STAGE DIRECTIONS IN BORISLAV MIHAJLOVIĆ MIHIZ’S PLAY BANOVIĆ STRAHINJA (Heritage, 2021)
Borislav Mihajlović Mihiz’s play Banović Strahinja excels as a text of special dramatic qualities, deeply connected with various aspects of stage directions. In order to show them, we analyzed how various dramatic elements, such as characterization, irony, space, and time, are represented in the context of stage directions. One of the most important aspects of Banović Strahinja is present in auctorial voice that can be seen both in the stage directions and as part of the primary text. Because of that, Mihiz’s play cannot be seen only as a reinterpretation of the famous Serbian epic poem, but also as a literary work in its own right firmly connected with modern theater tendencies.
Keywords: Borislav Mihajlović Mihiz, Banović Strahinja, didaskalia, stage directions, drama, auctorial voice, space in drama, characterization in drama.